Gestão democrática na escola: mecanismos de participação na Escola Estadual Augusto Antunes - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2018)
This work makes an analysis about the process of democratic management in a basic education school of the state public network of Amapá. The study was developed at Augusto Antunes State School, located in the central area of the city of Santana. For the theoretical approach, authors such as Gadotti, Lück, Paro, Hora and Mendonça, among others, were used. Based on bibliographic research and field research, a qualitative approach was taken and data were obtained from the application of questionnaires and semi-structured interviews with the current manager, pedagogical coordination, teacher, staff and students. A questionnaire with 05 questions was applied to all the informants with questions aimed at the fulfillment of the objectives and that tried to answer the problem of the research and verification of the hypotheses raised. Through the results obtained, it was concluded that the school is still in the process of rebuilding some of the bodies responsible for democratic management, such as the Student Guild and the Parents and Masters Association, and the current board seeks to promote democratic management as much as possible , by seeking to listen to the school community, to stimulate community participation in decision-making processes and to account for its management in the community, aiming at greater integration with the community and, at the same time, ensuring a better quality in the education of the students of the school.
Keywords: Gestão escolar democrática; Educação básica - Amapá; Comunidade escolar; CNPQ::CIENCIAS SOCIAIS APLICADAS